(untitled) (Agricultural Engineering, 2020)
The article presents determination methods of characteristic values of the reaction force course during the impact on fruit and vegetables to quickly assess their firmness or maturity. Moreover, various methods of modelling of the plant material behaviour during the impact that use differential equations, analytical equations, statistic models and numerical methods were discussed. Furthermore, dynamic methods that use fruit dropping on a rigid plate and measurement techniques that use a rigid element that hits a motionless fruit were reviewed and assessed. Advantages and disadvantages of these methods were presented. Statistical models are better for assessment of the bruise damage, but theoretical models are more useful for understanding the impact of various factors related to the impact damage. Various methods of application of rheological theories that describe a behaviour of the produce tissue treated as an elastic, elastic and plastic and visco-elastic were also described.